Crescimento, produção e composição química do Tifton 85 e características químicas de um latossolo vermelho sob doses de superfosfato triplo ou fosfato de araxá - Zuffo, Leodacir Francisco (2012)
This study aimed to evaluate the effects of single doses of superphosphate and Araxa phosphate growth, dry matter production and chemical composition of forage, forage nutrient uptake, and chemical attributes of an Oxisol cultivated with Tifton 85. The study was conducted in an Oxisol clayey, during the period December 2010 to March 2012, in an area located at latitude 24º 42'49'' S and longitude 53º 44' 35'' W. The experimental design was randomized blocks in factorial scheme 2x5, with two phosphorus sources (triple superphosphate and phosphate Araxá) and five P rates (0, 40, 80, 120, 160 kg P2O5 ha-1), with four replications. On growth and forage production were determined dry matter production, canopy height, tiller density, leaf area and leaf/stem ratio during three growing seasons at intervals of 28 days. The chemical composition was studied by determining the levels of CP, NDF, ADF, lignin, hemicellulose and cellulose, while the mineral composition was studied by determining the levels of macro minerals (phosphorus, potassium, calcium, sulfur and magnesium) and trace (iron, manganese, zinc and copper) in forage Tifton 85 produced by growth in four intervals of 28 days. The nutrient uptake was studied by estimating the extraction of phosphorus, potassium, calcium, magnesium, manganese, copper, zinc and iron in forage produced by Tifton 85 during the four growth periods of 28 days. In soil, the samples were taken towards the close of the experiment, at 0-10 and 0.10-0.20 m, determining the values of pH, phosphorus, potassium, calcium, magnesium, the sum of bases, CEC, base saturation, and levels of copper, manganese, zinc and iron. In the evaluations of dry matter production, canopy height, tiller density and leaf area was significant effect of phosphorus levels. The bromatological constituents were changed only by periods of growth due to climatic conditions of each period and the levels of macro and micro minerals in the forage of Tifton 85 were not affected by sources of variation studied, except for phosphorus and sulfur. Significant effect of doses of phosphorus sources only for the extraction of phosphorus and phosphorus contents of the soil. Phosphorus fertilization with Araxa phosphate or triple superphosphate increases dry matter production, canopy height, tillering and leaf area of Tifton 85. The phosphorus and sulfur in the dry matter are increased with the dose delivery Araxa phosphate or triple superphosphate. The extraction of soil phosphorus by Tifton 85 and phosphorus increases more significantly with the application of doses of Araxa phosphate altered without the other characteristics of soil